Detection of Chemical Weapon Agents Using Spectroscopic Probes: A Computational Study. (21st April 2020) - Braga, Letícia S.; Silva, Érika F.; Mancini, Daiana T.; da Rocha, Eduardo P.; da Cunha, Elaine F. F.; Ramalho, Teodorico C.
Abstract : Organophosphorus compounds are organic compounds widely employed in agriculture as well as in chemical weapons. The use in agriculture is due to their insecticidal properties. However, in chemical warfare, the use of organophosphorus is associated with acetylcholinesterase inhibition, which promotes the cholinergic syndromes. In this line, the fast detection of this class of compound is crucial for the determination of environmental exposure. This improved detection will naturally allow for more prompt courses of treatment depending on the contaminant findings. In this perspective, the dipyrrinone oxime (1 ) was employed for the detection of organophosphorus compounds that are employed as nerve agents, such as cyclosarin, sarin, soman, diethyl chlorophosphate, diisopropylfluorophosphate, 2-(dimethylamino)ethyl N, N-dimethylphosphoramidofluoridate, O-ethyl-S-[2-(diethylamino)ethyl]methylphosphonothioate, O-ethyl-S-[2(diisopropylamino)ethyl] methylphosphonothioate, and O, O-diethyl-S-[2-(diethylamino)ethyl] phosphorothioate, through fluorescent emission. The thermodynamics and kinetic parameters as well as spectroscopic properties of the complexes formed for 1 and all organophosphorus compounds previously cited were investigated by means of theoretical calculations. From our findings, only the diethyl chlorophosphate, 2-(dimethylamino)ethyl N, N-dimethylphosphoramidofluoridate, and O, O-diethyl-S-[2-(diethylamino)ethyl] phosphorothioate emitted fluorescence in the hexane, toluene, chloroform, dichloromethane, methanol, acetonitrile, water, and dimethyl sulfoxide solvents. The study of the absorption wavelength with the most polar solvent showed higher values compared to apolar solvents. In the same solvent, for instance, soman in hexane showed the lowest absorption wavelength value, 324.5 nm, and DCP the highest value, 330.8 nm. This behavior was observed in other tested solvents. The thermodynamic parameters indicate negative Gibbs free energy (Δ G ) values for the O-ethyl-S-[2(diisopropylamino)ethyl] methylphosphonothioate with 1 reaction. On the other hand, the sarin and cyclosarin revealed the lowest Gibbs free energy (Δ G ‡ ) values, being kinetically favorable and presenting more reactivity.